2021
DOI: 10.3390/biomedicines9020224
|View full text |Cite
|
Sign up to set email alerts
|

Anomalous Angiogenesis in Retina

Abstract: Age-related macular degeneration (AMD) may cause severe loss of vision or blindness, particularly in elderly people. Exudative AMD is characterized by the angiogenesis of blood vessels growing from underneath the macula, crossing the blood–retina barrier (which comprises Bruch’s membrane (BM) and the retinal pigmentation epithelium (RPE)), leaking blood and fluid into the retina and knocking off photoreceptors. Here, we simulate a computational model of angiogenesis from the choroid blood vessels via a cellula… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
6
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(6 citation statements)
references
References 66 publications
0
6
0
Order By: Relevance
“…At the beginning of the wet AMD, choriocapillaris degenerates with the formation of new leaky blood vessels that penetrate through the Bruch's membrane (Figure 2; Kaarniranta et al, 2013; McLeod et al, 2009; Muftuoglu et al, 2018; Qin & Rodrigues, 2008; Vega et al, 2021; Zajac‐Pytru et al, 2015). Changes in the choriocapillaris lead to neovascularization with haemorrhages, oedema and exudate formation and are followed by the degeneration and loss of RPE cells (Kaarniranta et al, 2013; McLeod et al, 2009; Muftuoglu et al, 2018; Qin & Rodrigues, 2008; Vega et al, 2021; Zajac‐Pytru et al, 2015). In the late stages of both disease forms of AMD, the RPE and choriocapillaris have become degenerated but the RPE degeneration is worse in dry AMD and choriocapillaris damage in the wet form (Biesemeier et al, 2014).…”
Section: Review Of the Literaturementioning
confidence: 99%
“…At the beginning of the wet AMD, choriocapillaris degenerates with the formation of new leaky blood vessels that penetrate through the Bruch's membrane (Figure 2; Kaarniranta et al, 2013; McLeod et al, 2009; Muftuoglu et al, 2018; Qin & Rodrigues, 2008; Vega et al, 2021; Zajac‐Pytru et al, 2015). Changes in the choriocapillaris lead to neovascularization with haemorrhages, oedema and exudate formation and are followed by the degeneration and loss of RPE cells (Kaarniranta et al, 2013; McLeod et al, 2009; Muftuoglu et al, 2018; Qin & Rodrigues, 2008; Vega et al, 2021; Zajac‐Pytru et al, 2015). In the late stages of both disease forms of AMD, the RPE and choriocapillaris have become degenerated but the RPE degeneration is worse in dry AMD and choriocapillaris damage in the wet form (Biesemeier et al, 2014).…”
Section: Review Of the Literaturementioning
confidence: 99%
“…Most of the building blocks for running an ISCT in the retina are already in place. When it comes to nAMD, there are already mechanistic models in place for the disease and intervention [136,283]. However, two main gaps still exist that are required to run successful ISCTs in retinal disease:…”
Section: Discussionmentioning
confidence: 99%
“…Abnormal growth factor secretion of RPE was one of the most common pathological progresses and it would lead to neovascularization in choroidal (wet AMD) and retina (proliferative DR). 35 , 36 RPE was the outer BRB and impaired RPE tight junction would cause retinal edema, such as macular edema secondary to DR. 37 Both neovascularization and retinal edema were two important causes of blindness for patients with retinal disorders. In this current study, it was found that GSPE treatment could moderate the abnormal SASP levels as well as impaired BRB by alleviating RPE cellular senescence.…”
Section: Discussionmentioning
confidence: 99%